MEDICAL PRACTICE MAL IN HEALTH LEGAL FRAMEWORK - Satria, Beni (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
The legal research method is a scientific activity based on certain methods, systematics, and thoughts, which aims to study one or several certain legal phenomena by analyzing them, except that, an in-depth examination of the legal facts is also held to then seek a solution. on the problems that arise in the symptoms in question. For this reason, research is carried out which includes methods. This research is a descriptive analysis which aims to describe in detail, systematically and thoroughly related to the problem. In this study, the data collection technique used is a library study. The literature study is carried out through secondary data sources, namely data that includes official documents, books,Malpractice in Article 11 paragraph (1) letter b in Law Number 6 of 1963 concerning Health Workers, which has been declared abolished by Law Number 23 of 1992 concerning Health. Based on the provisions of Article 11 paragraph (1) letter b of Law Number 6 of 1963, it can be used as a reference regarding malpractice, in the fields of administration, civil law, and criminal law. In medical malpractice which becomes an act against the law because of its nature, the will is often directed at the form of the act and not at the result. Culpa is usually only focused on the result. The adverse effects on the patient are not desired. In medical malpractice the form of action must be inconsistent with medical professional standards and standard operating procedures or at least contrary to normal general practice in the medical world.